Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Pasien Tuberkulosis Paru di Wilayah Kerja UPTD Puskesmas Sukabumi Kota Sukabumi - Muhammad Naufal Albar; Nunung Liawati; Waqid Sanjaya (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem with a high incidence rate, including in Sukabumi City. Treatment success in TB is highly dependent on patients’ adherence to medication, which is influenced by various factors, including family support. This study aimed to determine the relationship between family support and medication adherence among pulmonary tuberculosis patients in the working area of UPTD Puskesmas Sukabumi, Sukabumi City. This study used a quantitative design with a cross-sectional approach. The sample consisted of 48 respondents selected using total sampling technique. Data were collected using the Family Support Scale (FSS) to measure family support and the Morisky Medication Adherence Scale-8 (MMAS-8) to assess medication adherence. Data analysis was performed using univariate and bivariate analysis with the chi-square test at a significance level of 0.05. The results showed that most respondents had supportive family support and high medication adherence. Statistical analysis revealed a significant relationship between family support and medication adherence (p-value < 0.001). In conclusion, family support plays an important role in improving medication adherence among pulmonary TB patients. Therefore, active involvement of family members is essential to enhance treatment success.